Hilbert stratifolds and a Quillen type geometric description of cohomology for Hilbert manifolds - Kreck, Matthias; Tene, Haggai (Forum of mathematics. Sigma, 2018)
In this paper we use tools from differential topology to give a geometric description of cohomology for Hilbert manifolds. Our model is Quillen’s geometric description of cobordism groups for finite-dimensional smooth manifolds.